Phase 1 Trial of Amnion Cell Therapy for Ischemic Stroke - Phan, Thanh G.; Ma, Henry; Lim, Rebecca; Sobey, Christopher G.; Wallace, Euan M. (Frontiers in Neurology, 2018)
Background: There is increasing interest in stem cell therapy as another treatment modality in stroke, particularly for patients who are unable to receive endovascular clot retrieval (ECR) or thrombolysis therapies, or for whom standard treatment has failed. We have recently shown that human amniotic epithelial cells (hAECs) are effective in reducing infarct volume in different animal models of ischaemic stroke, including in non-human primates. hAEC therapy attenuated infarct growth and/or promoted functional recovery, even when administered 1-3 days after the onset of stroke. Methods: We now propose an open label Phase 1 dose escalation trial to assess the safety of allogeneic hAECs in stroke patients with a view to providing an evidence platform for future Phase 2 efficacy trials. We propose a modified 3+3 dose escalation study design with additional components for measuring magnetic resonance signal of efficacy as well as the effect of hAECs on immunosuppression after stroke. Result: The trial will commence in 2018. The findings will be published in peer reviewed journal. Conclusion: The trial is registered with ANZCTR (ACTRN12618000076279p).